2019
DOI: 10.1161/jaha.119.012482
|View full text |Cite
|
Sign up to set email alerts
|

Post–Myocardial Infarction Scar With Fat Deposition Shows Specific Electrophysiological Properties and Worse Outcome After Ventricular Tachycardia Ablation

Abstract: BackgroundFat deposition (FD) is part of the healing process after myocardial infarction. The characteristics of FD and its impact on the outcome in patients undergoing ventricular tachycardia (VT) ablation have not been thoroughly studied.Methods and ResultsWe studied consecutive patients undergoing post–myocardial infarction VT ablation with pre‐procedural cardiac computed tomography. FD was defined as intra‐myocardial attenuation ≤ −30 HU on computed tomography. Clinical, anatomical, and post‐procedural out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“… 13 The amount of infiltrating fat was also a predictor of VT recurrence after VT ablation in ICM patients. 14 Unlike these studies, our cohort consists of ICM patients with LV systolic dysfunction without any previous VT and thus is more representative of a broader ICM population at high risk for VAs. Our results show a lack of association between total intramyocardial fat mass and arrhythmic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 The amount of infiltrating fat was also a predictor of VT recurrence after VT ablation in ICM patients. 14 Unlike these studies, our cohort consists of ICM patients with LV systolic dysfunction without any previous VT and thus is more representative of a broader ICM population at high risk for VAs. Our results show a lack of association between total intramyocardial fat mass and arrhythmic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although intramyocardial fat is recognized to develop progressively after myocardial infarction and may be arrhythmogenic, no studies have examined the relationship between intramyocardial fat mass on CE-CT and the occurrence of VAs in a cohort of ICM patients with LV systolic dysfunction and no previous VAs. 8 , 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study involving a group of 72 patients undergoing ablation for VT, fat deposition within the myocardium was associated with worse outcomes and higher rates of VT recurrence. 12 Further strategies must be implemented before proceeding with invasive procedures in this patient population. Future implications may suggest broader and earlier use of CMR to evaluate the presence of lipomatous metaplasia in post-myocardial infarction scars and better risk stratification of patients prior to ablation to predict propensity for VT and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An association between lipomatus metaplasia and abnormal ventricular electrophysiology has been reported in both animal and clinical studies [ 110 , 128 ]. In this regard, electrophysiological studies demonstrated that lipomatus metaplasia, as depicted by CMR or CT, was strongly associated with scar age and size, lower bipolar and unipolar amplitudes and critical ventricular tachycardia circuit sites in patients with ischemic cardiomyopathy, suggesting its potential role in the generation of scar-related VT circuits in this setting [ 108 , 109 ]. Fragmented and isolated electrograms were also more frequently observed in areas with fat.…”
Section: Cardiac Adiposity and Ventricular Arrhythmiasmentioning
confidence: 99%